Paleomagnetism and tectonics of the Kamchatka region, northeastern Russia: implications for development and evolution of the northwest Pacific Basin. - Harbert, W; Kepezhinskas, Pavel A; Krylov, K; Grigoriev, V; Sokolov, Serguei; Aleksuitin, M; Heiphetz, A; Layer, P (PANGAEA, 2000)
The Kamchatka Peninsula of northeastern Russia is located along the northwestern margin of the Bering Sea and consists of zones of complexly deformed accreted terranes. Along the northern portion of the peninsula, progressing from then orthwestem Bering Sea inland the Olyutorskiy, Ukelayat, and Koryak superterranes area acreted to the Okhotsk-Chukotsk volcanic-plutonic bell in northern-most Kamchatka. A sedimentary sequence of Albian to Maastrichtian age overlap terranes and units of the Koryak superterrane and constrains their accretion time with this region of the North America plate. Ophiolite complexes, widespread within the Koryak superterrane, are associated with serpentinite melanges and some of the ophiolite terranes include large portions of weakly serpentinized hyperbasites, layered gabbro, sheeted dikes, and pillow basalts outcropping as internally coherent blocks within a sheared melange matrix. Interpretation of magnetic anomalies allow the correlation of the Ukelayat with the West Kamchatka and Sredinny Range superterranes. The Olyutorskiy composite terrane may be correlated with the central and southern Kamchatka Peninsula Litke, Eastern Ranges and Vetlov composite terranes. The most "out-board" of the central and southern Kamchatka Peninsula terranes is the Kronotsky composite terrane, weil exposed along the Kamchatka, Kronotsky and Shipunsky Capes. Using regional geological constraints, paleomagnetism, and plate kinematic models for the Pacific basin a regional model can be proposed in which accretion of the Koryak composite terrane to the North America plate occurs during the Campanian-Maastrichtian, followed by the accretion of the Olyutorskiy composite terrane in the Middle Eocene, and the Late Oligocene-Early Miocene collision of the Kronotsky composite terrane. A revised age estimate of a key overlapping sedirnentary sequence of the Koryak superterrane, calibrated with new Ar40/Ar39 data, supports its Late Cretaceous accretion age.
Tab. 1: Ar40/Ar39 results from Kuyul terrane, northeastern Russia
Keywords: Age, 40Ar/39Ar Argon-Argon; Age, dated; Age, dated standard deviation; Fraction; Geological sample; GEOS; Kuyul-terraine; Mass; Northeast Russia; Rock type; Sample ID